An adaptive output feedback motion tracking controller for robot manipulators: Uniform global asymptotic stability and experimentation - Yarza, Antonio; Santibanez, Victor; Moreno-Valenzuela, Javier (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with two important practical problems in motion control of robot manipulators: the measurement of joint velocities, which often results in noisy signals, and the uncertainty of parameters of the dynamic model. Adaptive output feedback controllers have been proposed in the literature in order to deal with these problems.
Keywords: adaptive control; robot control; nonlinear control; output feedback; Lyapunov UGAS stability